Advances in the Understanding of Two-Pore Domain TASK Potassium Channels and Their Potential as Therapeutic Targets - Xueming Fan; Yongzhi Lu; Guizhi Du; Jin Liu (Molecules, 2022)
TWIK-related acid-sensitive K+ (TASK) channels, including TASK-1, TASK-3, and TASK-5, are important members of the two-pore domain potassium (K2P) channel family. TASK-5 is not functionally expressed in the recombinant system. TASK channels are very sensitive to changes in extracellular pH and are active during all membrane potential periods. They are similar to other K2P channels in that they can create and use background-leaked potassium currents to stabilize resting membrane conductance and repolarize the action potential of excitable cells. TASK channels are expressed in both the nervous system and peripheral tissues, including excitable and non-excitable cells, and are widely engaged in pathophysiological phenomena, such as respiratory stimulation, pulmonary hypertension, arrhythmia, aldosterone secretion, cancers, anesthesia, neurological disorders, glucose homeostasis, and visual sensitivity. Therefore, they are important targets for innovative drug development. In this review, we emphasized the recent advances in our understanding of the biophysical properties, gating profiles, and biological roles of TASK channels. Given the different localization ranges and biologically relevant functions of TASK-1 and TASK-3 channels, the development of compounds that selectively target TASK-1 and TASK-3 channels is also summarized based on data reported in the literature.